ℋ∞ Stability Conditions for Fuzzy Neural Networks. (15th February 2012) - Ahn, Choon Ki
Abstract : This paper presents a novel approach to assess the stability of fuzzy neural networks. First, we propose a new condition for theℋ ∞ stability of fuzzy neural networks. Second, a newℋ ∞ stability condition based on linear matrix inequality (LMI) is presented for fuzzy neural networks. These conditions also ensure asymptotic stability without external input.